Viral and cellular N6-methyladenosine and N6, 2′-O-dimethyladenosine epitranscriptomes in the KSHV life cycle. (January 2018) - Tan, Brandon; Liu, Hui; Zhang, Songyao; da Silva, Suzane; Zhang, Lin; Meng, Jia; Cui, Xiaodong; Yuan, Hongfeng; Sorel, Océane; Zhang, Shao-Wu; Huang, Yufei; Gao, Shou-Jiang
Abstract N6 -methyladenosine (m6 A) and N6, 2′-O -dimethyladenosine (m6 Am) modifications (m6 A/m) of messenger RNA mediate diverse cellular functions. Oncogenic Kaposi's sarcoma-associated herpesvirus (KSHV) has latent and lytic replication phases that are essential for the development of KSHV-associated cancers. To date, the role of m6 A/m in KSHV replication and tumorigenesis is unclear. Here, we provide mechanistic insights by examining the viral and cellular m6 A/m epitranscriptomes during KSHV latent and lytic infection. KSHV transcripts contain abundant m6 A/m modifications during latent and lytic replication, and these modifications are highly conserved among different cell types and infection systems. Knockdown of YTHDF2 enhanced lytic replication by impeding KSHV RNA degradation. YTHDF2 binds to viral transcripts and differentially mediates their stability. KSHV latent infection induces 5′ untranslated region (UTR) hypomethylation and 3′UTR hypermethylation of the cellular epitranscriptome, regulating oncogenic and epithelial-mesenchymal transition pathways. KSHV lytic replication induces dynamic reprogramming of epitranscriptome, regulating pathways that control lytic replication. These results reveal a critical role of m6 A/m modifications in KSHV lifecycle and provide rich resources for future investigations. This study reports the viral and cellularN 6 -methyladenosine (m6 A) andN 6, 2′-O -dimethyladenosine (m6 Am) epitranscriptomes during KSHV latent and lytic infection, and shows that lytic replication induces dynamic epitranscriptome reprogramming of host pathways that control this process.